Recent advances in understanding of meiosis initiation and the apomictic pathway in plants - Wang, Chung-Ju R.; Tseng, Ching-Chih (Frontiers in Plant Science, 2014)
Meiosis, a specialized cell division to produce haploid cells, marks the transition from a sporophytic to a gametophytic generation in the life cycle of plants. In angiosperms, meiosis takes place in sporogenous cells that develop de novo from somatic cells in anthers or ovules. A successful transition from the mitotic cycle to the meiotic program in sporogenous cells is crucial for sexual reproduction. By contrast, when meiosis is bypassed or a mitosis-like division occurs to produce unreduced cells, followed by the development of an embryo sac, clonal seeds can be produced by apomixis, an asexual reproduction pathway found in 400 species of flowering plants. An understanding of the regulation of entry into meiosis and molecular mechanisms of apomictic pathway will provide vital insight into reproduction for plant breeding. Recent findings suggest that AM1/SWI1 may be the key gene for entry into meiosis, and increasing evidence has shown that the apomictic pathway is epigenetically controlled. However, the mechanism for the initiation of meiosis during sexual reproduction or for its omission in the apomictic pathway still remains largely unknown. Here we review the current understanding of meiosis initiation and the apomictic pathway and raised several questions that are awaiting further investigation.